Appendiceal carcinoid tumours: indications for right hemicolectomy and appendectomy - Connell, James O. (International Surgery Journal, 2016)
This is a review of the current best evidence pertaining to the surgical management of appendiceal carcinoid tumours and outlines a set of recommendations for right hemi colectomy and appendectomy in patients with histologically confirmed appendiceal carcinoid tumour. The management of appendiceal carcinoids is complex and several factors have been shown to influence prognosis. Surgical management is the mainstay of treatment with appendectomy and right hemi-colectomy being the surgical approaches of choice. There is still much debate as to the indications for appendectomy or right hemicolectomy. From our search of the literature eight studies were included for review and one set of guidelines. All studies included were retrospective cohort studies. There were no Cochrane reviews or systematic reviews pertaining to the management of appendiceal carcinoid tumours. There is conflicting evidence as to the management of tumours greater than 2cm. Involvement of the base of the appendix and mesoppendix involvement while not supported by the literature are supported by consensus expert opinion in two sets of guidelines as an indication for right hemicolectomy.